MOLT RELATED SENSITIVITY OF FRESHWATER PRAWN MACROBRACHIUM KISTNENSIS TO NAPHTHALENE - NAGABHUSHANAM, R.; JAISWAL, KEWAL B.; SAROJINI, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
An attempt has been made to determine sensitivity differences between the intermolt and different known molt stages of freshwater prawn, Macrobrachium kistnensis exposed to naphthalene Further the effects of various concentrations of naphthalene on molting success and survival have also been studied. The prawns in the proecdystal stage were more sensitive to naphthalene. The exuvia weight of prawn exposed to 0 23828 ppm was 165-0.577 mg whereas exuvia of prawn exposed to 0.29785 ppm, O 3971 ppm, 0.5957 ppm and 1.1974 ppm of naphthalene were 175-1- 0.577 mg, 18.0-0 816 mg, 1925-10957 mg and 20.5-0.577 mg respectively. Exposure to the different concentrations of naphthalene caused an increase in molt frequency. Prawns exposed to high concentration of naphthalene (1.1914 ppm) showed an 100% mortality after 3rd molt. The duration of the intermolt period decreased from 20.8 days to 142 days for 1st molt, 42.6 days to 25.2 days for 2nd molt and 58 6 days to 35.75 days for 3rd molt. After 3rd molt all prawns died.